2021
DOI: 10.3389/fmars.2021.673045
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Matter: Assessing the Impacts of a Marine Protected Area on Human Wellbeing and Relational Values in Southern Tanzania

Abstract: The push to meet global marine conservation targets has significantly increased the scope and scale of marine protected areas (MPAs) worldwide. While the benefits derived from MPA establishment are often optimistically framed as a “win-win” for both marine biodiversity and for the wellbeing of coastal peoples, this assumption is challenged for several reasons, including the fact that current science and practice frequently fails to account for the full impact of MPAs on human wellbeing. This context poses a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…According to our model this agency is required to establish the bidirectional relationship from which relational values emerge. Several studies have found that agency is important for certain environmental values—and that agency can feel threatened by conservation policies (Baker et al, 2021; Chapman et al, 2019; Kaltenborn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to our model this agency is required to establish the bidirectional relationship from which relational values emerge. Several studies have found that agency is important for certain environmental values—and that agency can feel threatened by conservation policies (Baker et al, 2021; Chapman et al, 2019; Kaltenborn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Neuteleers suggests we consider relational values as motivated by 'reasons of love or care, or as meaningfulness ' (2020, p. 477). Relational wellbeing, as one dimension of human wellbeing, can be considered to encompass not only human-human relationships, but also human-nonhuman ones as expressed by relational values (Baker et al, 2021).…”
Section: Eudaimonia In and Beyond Care: B→a As Eudaimonic Aspectmentioning
confidence: 99%
See 3 more Smart Citations